Juvesenility = 소망 - Ch'ae Man-sik (바이링궐 에디션 한국 대표 소설, 2015)
"In "Juvesenility" the philistine first-person narrator reveals her snobbery and her ignorance of reality through her failure to understand her husband's eccentricity. ... Her husband's abnormal behavior derives from his creed that to survive in an upside-down world he too must act upside-down, a statement that carries overtones of ill health and distorted reality." --back cover.